Sulfate Kinetics and Adsorption Studies on a Zeolite/Polyammonium Cation Composite for Environmental Remediation - Escudey-Castro, A; Escudey-Castro, A; Pizarro-Arriagada, C; Pizarro-Arriagada, C; Gacitua-Santalices, M; Gacitua-Santalices, M (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Sulfide mineral mining produces highly sulfate-contaminated wastewater which needs to be treated before disposal. A composite material was made from natural zeolite (NZ) and Superfloc® SC-581, a polyammonium cationic polymer. The resulting modified zeolite (MZ) demonstrated improved capacity for sulfate abatement from wastewater compared to NZ. Above pH 4.0, MZ retained positive surface charge while NZ remained negative. The effect of the ionic strength on the adsorption process was evaluated. Sulfate adsorption capacity was assessed and revealed MZ to be superior to NZ in all cases. Adsorption kinetics reached equilibrium after 10–12 h, with MZ adsorption being twice that of NZ; data fitted a pseudo-second order kinetic model. Adsorption isotherms reflected the high capacity of MZ for sulfate adsorption with maximum of 3.1 mg g−1, while NZ only achieved 1.5 mg g−1. The process corresponds to heterogeneous partially reversible adsorption of ionic species over the solid adsorbent. Langmuir–Freundlich parameters revealed that adsorption over MZ corresponds to an interaction eight times stronger than that on NZ. The sulfate adsorption pattern changes with ionic strength. Taken together, the composite formed between natural zeolite and polyammonium represents an adsorbent that maintains the adsorption capacity of zeolite and proves suitable for anionic species removal. Further prospect considers the testing of the composite with other anionic pollutants (arsenate, phosphate, perchlorate, etc.). © 2021 by the authors. Licensee MDPI, Basel, Switzerland.